Evaluasi Kinerja Keuangan dalam Mengelola Dana Desa dengan Menilai Efisiensi dan Pertumbuhan Melalui Rasio-rasio Tertentu - Kalypso Digantari; Aulia rahman (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
This research aims to evaluate financial performance in managing village funds with a focus on assessing efficiency and growth using certain ratios. This research method involves financial ratio analysis which includes liquidity ratios, profitability ratios, and growth ratios. The data used comes from village fund financial reports for a certain period. The results of the analysis will provide an in-depth understanding of the efficiency of village fund management and its impact on economic growth at the local level. This research can provide guidance for the government and related parties in improving village fund management policies to achieve sustainable development goals.